Overview on Quail Management, Production and Its Physiological Performance (Article Review) - Al-Sofee, Khalid Hadi Mustafa; Al-Hamed, Anwar Anwar Younis; Abdul-Majeed, Abdullah Fathi; Osman, Mohammad Ahmed Al-Sagheer Hussain (Journal of agricultural, environmental and veterinary sciences, 2025)
This review aims to provide information on the characteristics of quail production and management, identify its nutritional requirements, and define its role as a key component of livestock production. The quail (Coturnix) is known by many names in the Arabic language, and there are many types of it, each of which is divided into several varieties or subspecies. The Japanese quail (Coturnix coturnix japonica) is the most common and widely used in the poultry industry and scientific research. Quail, on the other hand, is a small, domesticated wild bird known for its quick, agile movements and distinctive voice. Its weight ranges from 160 to 250 grams, and it reaches sexual maturity at 5 weeks of age. It is a dual-purpose bird, producing both eggs and meat, with an annual egg production ranging from 250 to 300 eggs. Therefore, quail has significantly contributed to alleviating the meat and egg crisis in the world. In the 1960s, researchers in Japan and neighboring Asian countries focused on developing new quail breeds characterized by high body weights and high egg production when reared for 8 weeks using modern intensive rearing systems, and the Japanese quail became the most widely used in the poultry industry and scientific research because it is an important economic bird with low care costs, high egg production, rapid adaptation, and resistance to environmental conditions and diseases. It is also suitable for intensive rearing in small spaces, in addition to its short generation period (3-4 generations per year).